2017
DOI: 10.1186/s12885-017-3885-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplement use among cancer survivors and the general population: a nation-wide cross-sectional study

Abstract: BackgroundUse of dietary supplements among cancer survivors is common and controversial, but information on the amount of nutrients from supplements among cancer survivors is limited. We examined the amount of nutrients and their contribution to total nutrient intake from supplements and compared these data between cancer survivors and cancer-free individuals. We also identified factors associated with supplement use among cancer survivors.MethodsWe identified 400 cancer survivors and 10,387 cancer-free indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 29 publications
1
39
2
Order By: Relevance
“…A nation-wide crosssectional Korean study also found that Korean cancer survivors use DS (33.3%) more frequently than cancer-free individuals (22.1%). 9) In previous study on general population, factors associated with more frequent use of DS were female gender (P=0.041), Caucasian (P<0.001), and older age (mean age, 56.98 years versus 53.34 years; P<0.001), and higher number of chronic conditions (P=0.004). 10) In a study of American cancer survivors, female gender (odds ratio [OR], 1.72; 95% confidence interval [CI], 1.25-2.36) and higher education levels (OR, 5.44; 95% CI, 2.98-9.93) were associated with DS use.…”
Section: Introductionmentioning
confidence: 86%
“…A nation-wide crosssectional Korean study also found that Korean cancer survivors use DS (33.3%) more frequently than cancer-free individuals (22.1%). 9) In previous study on general population, factors associated with more frequent use of DS were female gender (P=0.041), Caucasian (P<0.001), and older age (mean age, 56.98 years versus 53.34 years; P<0.001), and higher number of chronic conditions (P=0.004). 10) In a study of American cancer survivors, female gender (odds ratio [OR], 1.72; 95% confidence interval [CI], 1.25-2.36) and higher education levels (OR, 5.44; 95% CI, 2.98-9.93) were associated with DS use.…”
Section: Introductionmentioning
confidence: 86%
“…Apigenin is present in many fruits, vegetables, teas, and herbal supplements [1]. Use of herbal supplements is increasing in the general population [2], and is even higher among cancer patients [3, 4]. Therefore, interest in the role of apigenin (4′,5,7,-trihydroxyflavone) in cancer prevention and treatment has been increasing [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that cancer survivors used more riboflavin, folate, and iron from foods (P < 0.05 for each), and also had higher intakes of calcium (P = 0.05) and vitamin C (P = 0.01) from foods and supplements than cancer-free individuals. In female cancer survivors, those with higher education level, moderate physical activity, low vegetable intake, and high circulating vitamin D levels had higher supplement intake (13). This study shows that there is a trend to higher level of supplements intake in cancer cases.…”
Section: Discussionmentioning
confidence: 61%